ASSERTIVENESS AND ATTITUDES OF HIV/AIDS ORPHANED GIRLS TOWARDS EDUCATION IN KAMPALA (UGANDA). - Kitara, David Lagoro; Amongin, Hellen Christine; Oonyu, Joseph C; Baguma, Peter K (African Journal of Infectious Diseases (AJID), 2005)
Whereas HIV/AIDS prevalence has been declining in Uganda from 30% to less than 10% in the last 2 decades, the number of HIV/AIDS orphaned girls in secondary schools is still high and girl children have tended to carry the heaviest burdens of family responsibilities thereby adversely affecting their assertiveness and attitudes towards education. Assertiveness is a critical life skill that enables a person to state an opinion, claim a right, or establish authority and it is important to improve attitude towards education. This study examined the relationship between assertiveness and attitude towards education of HIV/AIDS orphaned and non-orphaned adolescent school girls in Kampala. The California Psychological Inventory (CPI) Dominance (Do) Assertiveness Scale and the Attitude Scale were administered to 225 students consecutively selected from 6 secondary schools in Kampala. HIV/AIDS Orphaned girls had lower levels of assertiveness and most had a negative attitude towards education compared to non-orphaned girls. Girls orphaned to HIV/AIDS were less assertive compared to those orphaned by other causes. There was a positive relationship between assertiveness and attitude towards education among orphaned adolescent secondary school girls in Kampala. Girls orphaned to HIV/AIDS were less assertive compared to other school girls and have a poor attitude towards education.